Influencia del programa vaso de leche en la alimnetación de los beneficiarios de la provincia de virú: en el año 2012 - Garcia Cruz, Sofia Eusebia (2013)
This thesis was carried out with the purpose to analyze the impact of the Program of the Glass of Milk in the power of the beneficiaries of the Viru District in the period 2012. It has been considered the type of applied research, on the basis of an explanatory design, and the sample consisted of 212 beneficiaries, with whom they work by applying the methods and techniques of quantitative and qualitative research. The agenda of the Glass of Milk (PVL), is a social program created to offer, a daily ration of food to a population considered vulnerable, with the purpose to help it overcome the food insecurity in the that is. The activities of this program, carried out with the strong involvement of the community, would have as their ultimate goal raise their nutritional level and thus contribute to improving the quality of life of this group which, by its precarious economic situation, it would not be in a position to meet their basic needs. In addition, an important particularity of this Program, has been linked to the municipal management and be basically operated by committees of beneficiaries of the program itself, bringing as an add-on product, an important progress in the organized social mobilization, and generating a notorious area for developing citizen participation, and the formation of a growing contingent of leaders, especially within the popular movement of women.